Mapping the Research Landscape: A Bibliometric Analysis of Innovative Work Behavior and Leadership Trends - Jadmiko, Purbo; Pratama, Putra; Huddin, Muhammad Nurhaula (Universitas Muhammadiyah Tangerang, 2025)
This study explores research trends and thematic patterns at the intersection of Innovative Work Behavior (IWB) and leadership through a bibliometric analysis using the Scopus database. The analysis includes 427 publications from 2019 to 2024. The bibliometric analysis was conducted using VOSviewer, a tool widely recognized for visualizing bibliometric networks. The software facilitated the identification of co-occurrence patterns, and thematic clusters. Keyword co-occurrence analysis revealed dominant themes such as